A Validated Instrument to Assess Representational Interpretation Skills in Basic Chemistry Laws: A Development and Validation Study - Lisa Tania; Andrian Saputra (Institute of Multidisciplinary Research and Community Service, 2025)
The abstract and symbolic nature of chemistry presents significant learning challenges for students, particularly in the understanding of foundational concepts through a variety of representations. It's tougher to teach well, especially in Indonesia, because there are not many trustworthy instruments to measure students' interpretative skills, which are very important for representational competence. The goal of this study was to fill this gap by creating and testing a reliable assessment tool called the Assessment of Representational Competence in Fundamental Chemical Laws (ARC-FCL), which was meant to measure the interpretative skills of Indonesian senior high school students. The Define, Design, and Develop stages of the 4D model were employed in the Research and Development process of this study design. The Kozma-Russell framework and the Three-Dimensional Learning Assessment Protocol (3D-LAP) helped shape the instrument's development. The ARC-FCL test has two levels of multiple-choice and essay questions about the laws of Lavoisier, Dalton, and Gay-Lussac. Two chemistry education professors and one experienced instructor reviewed the content to ensure its validity. Researchers got real-world data for psychometric analysis from 30 11th-grade students at a senior high school in Lampung, Indonesia. The study looked at item validity using Pearson correlation, item discrimination, and internal consistency reliability using Cronbach alpha. All three designed items had great validity, with correlation values over the key threshold of 0.361 and good discrimination indices between 0.50 and 0.75. The instrument was somewhat reliable, with a Cronbach alpha coefficient of 0.572. This is fine for a formative diagnostic tool at this early stage of development. Item analysis also showed that students had the most trouble with the question about the Law of Multiple Proportions. In conclusion, this study developed a valuable and valid instrument for identifying the specific challenges faced by students when attempting to comprehend sub-microscopic representations of fundamental chemical principles. As a formative assessment instrument that fits with the Kurikulum Merdeka, the ARC-FCL is quite useful for Indonesian teachers. It encourages a move from memorizing things by heart to comprehending them better and learning how to do science. Future work should be focused on adding more items to the bank to make it more reliable and cover more ground. Keywords: representational competence, assessment instrument, interpretive skills, basic chemical laws, 4D model, instrument validation.